Business Strategy, Capital Intensity, Tax Avoidance: Good Corporate Governance as a Moderator - Meidita Andrilia; Hari Setiyawati (Jurnal Akuntansi, 2025)
This research begins with phenomenon regarding the difference in interests between the government and taxpayers that can cause tax avoidance actions. This study aims to determine the influence of business strategy and capital intensity on tax avoidance with good corporate governance as a moderating variable. This research was conducted on companies listed on the Indonesia Stock Exchange from 2018 to 2022, using causality data. The sample was determined using purposive sampling, consisting of 36 companies. The data analysis techniques used are moderated and multiple regression analysis using e-views 13. The novelty research through the role of good corporate governance as moderation. The research results show that business strategy has no effect on tax avoidance while capital intensity has a significant effect. Good corporate governance cannot moderate this influence. The implementation of business strategies and good corporate governance has no influence in reducing tax avoidance, so it’s necessary to consider other external factors.